DIELECTRIC SPECTROSCOPY IN CRUSTAL ROCKS: PRELIMINARY RESULTS FROM NORTHEASTERN SICILY (ITALY) AND THE GULF OF CORINTH (GREECE) - Triantis, D.; Stavrakas, I.; Anastasiadis, C.; Vallianatos, F.; Kershaw, S. (Bulletin of the Geological Society of Greece, 2004)
Dielectric response was studied on two samples of manganese- and iron bearing rock materials of two different geological origins, one from Northeastern Sicily (Italy) and one from the Southern Gulf of Corinth (Greece). The study of the dielectric properties is a flexible non destructive testing method. The technique is based on the application of a single- frequency AC electric field to the sample and the measurement of the amplitude and phase of its response. In the present work the broadband dielectric relaxation spectroscopy technique was applied in the frequency range from 1kHz to 1MHz. The hydrated samples, of the above rock materials, that give rise to high values of both the real and imaginary part of the complex dielectric permittivity function are due to interfacial polarization mechanisms attributed to pore water. The two dry samples exhibit much lower values with respect to the hydrated ones while they have a big differentiation between their own permittivity values as well as between the shapes of their dielectric responses. This can be attributed to different origins of geotectonic deformation of the samples.